Semiotics of ritual: Cultural meaning in Javanese traditional wedding symbols - Nihayatul Karimah; Prilla Lukis Wediyantoro (Universitas Merdeka Malang, 2025)
Symbolism uses symbols to illustrate a deeper meaning than their literal meaning, which is vital in various cultural practices. In Javanese weddings, symbolism is deeply embedded in various ceremonies and rituals, each containing a deep meaning. These symbols reflect Javanese society's values, beliefs, and traditions, emphasizing harmony, unity, and a sense of tolerance. This study aims to describe and explain the symbols of Javaese traditional weddings in Pandansari Village, Malang Regency. The findings reveal that the Javanese traditional wedding in Pandansari Village has three main stages: pre-wedding, the wedding, and the post-wedding ceremony, with their sub-stages. The pre-wedding ceremony consists of three processions, the wedding has three processions, while the post-wedding ceremony has only one. Moreover, there are more sub-processions with their meanings and philosophies among the processions. Based on the limitations of this study, future study is expected to expand the scope of analysis by examining more symbols from other traditional wedding ceremonies in Javanese and other cultures and analyzing the meaning of the symbols in them to get a comparison and new understanding.